Learning Pancasila Through Garuda AR Media - Candra Cuga; Ni Nyoman Nofi Dwi Astuti; Yuli Adhani (Universitas Pendidikan Ganesha, 2024)
The lack of digital media has an impact on low student learning outcomes. This study aims to develop augmented reality-based civics learning media on the Garuda Pancasila material for grade IV in elementary schools. This study uses a mixed method, namely a quantitative and qualitative approach with quasi-experimental and descriptive techniques. The study subjects were media experts, material experts, and user experts. The subjects of the trial were grade IV elementary school students. The data collection techniques used in this study were observation, questionnaires, and documentation. The data collection instrument used a questionnaire sheet. The data analysis technique used qualitative and quantitative descriptive analysis. The study results, namely the validation results obtained from material, media, and user experts (users) with consecutive percentages included in the very feasible category. The trial results were limited to students, and a questionnaire was provided that obtained a percentage of the very good category. Thus, it can be concluded that the developed learning media is feasible for elementary school civics learning. The developed learning media can stimulate students' mindsets in thinking critically and independently and increase students' motivation and interest in learning. This research implies that its results can significantly contribute to developing technology-based interactive learning methods, significantly augmented reality (AR), which can enrich the Pancasila teaching process in schools.